Segregation Hurts Voices of Youth with Disabilities and Their Families in India - Antony, Pavan John.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Segregation Hurts is a book that explores the stories of six families who have children with disabilities. The families who reside in the south west of India shared their daily experiences living with a child with a disability. Irrespective of the diverse socio-economic statuses and religious beliefs, families shared common challenges raising a child with a disability in the Indian society. These children faced exclusion and denial of admission to local public schools due to their disability and they were forced to seek admission to a special school in their neighbouring community. Public schools in India continue to deny admission to millions of children due to their disabilities and are an invisible minority in the society. This book provides a novel and unique perspective about the nuances and daily struggles of families who are silenced and shut out due to the shortcomings and oppressive nature of the education system. Further an indepth analysis and critique is made of the treatment and education of children with disabilities in India. Dr. Antony is a strong advocate of inclusive schooling and this book will share his expertise within international contexts. (3z(BI highly recommend Dr. Antony$1 (Bs book. It gives a new insight into the life and lessons of Gandhi.(3y (B- Arun Gandhi, President, Gandhi Worldwide Education Institute, Rochester, NY, USA. Pavan Antony has written a compelling overview of the education of children with disabilities in India through six stories. There are commonalities in the families$1 (Bs experiences, even though they come from different backgrounds. The candid conversations the researcher had with the families brings their hopes, fears and dreams to life. The move to inclusive practices in a developing country is difficult and Pavan Antony captures the macro and micro challenges through this powerful narrative. - Dr. Vianne Timmons, President and Vice-Chancellor, University of Regina, Canada. Pavan Antony has given us deeper insight into the lives of families that include people with disabilities in India. Through the stories of six individuals, their parents and siblings, the variables of class, religious tradition, cultural identify and human resilience are explored. Pavan$1 (Bs book provides an enriching cultural lens with which to explore disability, humanity and the dignity of each person. - Barbara Trader, Executive Director of TASH, Washington,s
Keywords: Education; Education; Education (general).